Striving to Teach Versus Modern Realia - Nikishyna, Anzhela (Educational Challenges, 2021)
There have always been challenges confronting both teachers and students in the process of sharing knowledge and skills. The purpose of the article is to analyze the situation that has become even more demanding due to the changes connected with the implementation of distance learning. Theoretical and methodological base of the research consists of an approach connected with the use of such methods as analysis, generalization and interpretation of the psychological theory of motivation and the concept of amotivation and its consequences; observation of the current educational situation with regard to its active participants. Results focus on modern realia, when the educational conditions have been greatly changed in connection with the pandemic situation, it is possible to notice decrease of motivation among the students. Students tend to miss classes as they believe that teaching can be ineffective, prefer not to answer during the lesson, take time in handing in their homework, fellow students influence their choice of being less diligent. Technical problems or inability to participate in an active way in the process of the lesson can really worsen the situation with the desire to get proper knowledge. Conclusion. That is why teaching big group of students and individual approach when conducting online lessons can be so challenging to teachers. It can lead to burning out while working and teacher wellbeing is also at risk, its great importance has been once again proven and highlighted.